Determinants of News Sharing Behavior on Social Media - Thompson, Nik; Wang, X.; Daya, P. (IACIS, 2019)
© 2019, © 2019 International Association for Computer Information Systems. Social media is relied upon as a single portal for entertainment, communication, and news. To understand determinants of new sharing, we empirically evaluate data from 188 Facebook users with PLS structural equation modelling. Results support the significant influence of information sharing and status seeking gratifications on news sharing, and that this significance varies across contexts. We find that status seeking gratification has a stronger effect on news sharing when news quality is more emphasized. In other words, sharing low-quality news can be damaging to an individual’s status and they try to avoid it. However, information sharing gratification has a stronger effect on news sharing for those individuals who rely more on credibility and may be employing more heuristic selection approaches. This work has opened up new opportunities for further research and it is hoped that this may contribute to improving the quality and experience of news sharing in social media.